New species of Pseudanos Winterbottom, 1980 (Characiformes: Anostomidae), with notes on the taxonomy of P. gracilis and P. trimaculatus - Birindelli, José L. O.; Lima, Flávio C. T.; Britski, Heraldo A. (Zootaxa, 2012)
A new species of Pseudanos (Characiformes, Anostomidae) is described from the Rio Negro in Brazil, and the Río Ca-siquiare and Río Atabapo, in Venezuela. Specimens of the new species were previously mistakenly identified as Pseuda-nos gracilis. The new species is diagnosed by having three branchiostegal rays (vs. four in P. gracilis and most specimensof P. winterbottomi), dark transversal bars on dorsum absent (vs. present in P. trimaculatus), dark spots present on the cen-ter of each body scale, forming conspicuous, straight dark lines (vs. dark spots absent in P. gracilis and in some specimensof P. trimaculatus), four midlateral dark blotches on body (vs. usually two, sometimes three or four in P. trimaculatus, orbody lacking midlateral blotches and presenting instead a broad midlateral stripe in P. winterbottomi), angle of dorsal andventralmost radii of body scales between 40° and 90° (vs. angle between 110° and 180° in P. gracilis and P. trimaculatus),and cranial fontanel opened along its entire length (vs. cranial fontanel partially closed in P. trimaculatus). Type specimensand extensive additional material of Pseudanos gracilis and P. trimaculatus were examined and comments on the taxon-omy of both species are provided. Pseudanos irinae is herein considered a junior synonym of P. trimaculatus. In addition, an updated key to identification of valid species of Pseudanos is presented.